Percepción de estudiantes de medicina veterinaria de la universidad Antonio Nariño y propietarios de mascotas que asisten a la clínica veterinaria de la universidad Antonio Nariño sobre el uso de medicina alternativa - Avendaño Ruiz, Alicia; Castillo Carreño, Jeison David; Molina Muñoz, Ángela Sofia (Universidad Antonio Nariño, 2021)
Thanks to the growing interest worldwide in complementary and alternative medicine (CAM), in the human medicine area, which is notorious in different places of the world, such as Latin America where normatives have already been generated to regulated CAMs. Europe where it has begun to implement the use of integrative medicine, which has led to an increase in scientific research of these medicines, while in the field of veterinary medicine due to the few studies based on these, there is no marked increase in use or generations of policies for those and therefore decreases the chance of a integrative veterinary medicine. The aim of our study was to know the perception, knowledge and interest of pet owner and veterinary medicine students from the Antonio Nariño University who attended the veterinary clinic, investigate which is the preference of these over complementary medicine and carry out the corresponding literature evaluation on this. The results of this study imply that the majority of the surveyed people 78% recognize that it is alternative medicine, which show us since the beggining of the survey desinformation of alternative medicine which is also reflected in the use that it has had, 6% of the 100% of the respondents have use alternative medicine as a form and these also are willing to use it, as can be demonstrated in another result where is it shown that of the respondents, 57% have not use alternative medicine, most of the respondents would integrate alternative and traditional medicine if they became more knowledgeable about them. Finally it was established in our study that thanks to the scarcity in studies about veterinary alternative medicine it direcly affects perception of MACs to the public.